TEMUAN POST MORTEM AKIBAT KERACUNAN METANOL - Masnu’atul Hamidah; Kunthi Yulianti (Universitas Udayana, 2017)
Incident of methanol toxicity increases as high as alcohol consumption pattern in community. The high price of alcohol become one of factors that encourage people to get the high level alcohol with the lowest price. It was done by giving addictive substances, like methanol. With the phenomenon, this research is done to know how can methanol has death effect and what abnormalities can be found in the victims.It is a descriptive research to get an explanation about post mortem characteristics in methanol toxicity victims. This research takes secondary data of Victim Examination Report from 2008 until 2013 at RSUP Sanglah Denpasar.Amount of the samples are 10. It is found asphyxia sign that is ptechie dan vascular dilatation in many organs. Toxicology examination shows methanol level below 100 ppm in 10% samples, 20% samples has toxic dose 100-300 ppm, 40% samples has methanol level 300-1500 ppm, and 30% samples has extremely level of methanol above 1500 ppm. Histopathologic examination shows vascular dilatation at liver, kidney, lung, and brain. Death of methanol toxicity not only influenced by the dose of methanol, but also the existence of predisposition factor such as disease. It needs more research to know the specific abnormalities of methanol toxicity.